Growth Velocity of the Preterm Infant Managed with a Standardized Nutritional Protocol in a Tertiary Care Hospital (Faridpur Medical College Journal, 2021)
Prematurity is one of the major causes of neonatal death in developing countries like Bangladesh. Appropriate protocol for nutritional support of the preterm infants is essential to achieve a postnatal growth rate similar to that of a normal fetus. Objective of the study was to assess the effects of the existing nutritional support protocol of Bangabandhu Sheikh Mujib Medical University (BSMMU) in the early postnatal growth velocity of the preterm infants.This quasi-experimental study was conducted in the Department of Neonatology, BSMMU, Bangladesh from January to December 2015. All admitted infants aged